406 REVIEWING THE DYSPLASIA DURING LONG FU OF BARRETT'S ESOPHAGUS. SHOULD WE RELY ON THE DIAGNOSIS OF DYSPLASIA?. (14th September 2020) - Szachnowicz, S; Duarte, A; Mattos, B; Iriya, K; Bianchi, E; Seguro, F; da Rocha, J; Sallum, R; Cecconello, I
Abstract:  : Barrett' s esophagus (BE) is a complication of severe gastroesophageal reflux disease (GERD). The major concern aspect is its association to dysplasia and esophageal adenocarcinoma. The endoscopic treatment of the epithelium, as well as the follow-up (FU) period, should be guided according to the diagnosis and the worst degree of dysplasia found in the last endoscopies. However, we are aware of the great difficulty and variation among pathologists in diagnosing and grading dysplasia in BE. Methods: Aim: Review new diagnoses of low- and high-grade dysplasia (LGD and HGD) in BE with specialized pathologists during long-term FU in clinical or surgical treatment for GERD From January 1980 to July 2019, 738 patients with BE were FU (average of 98 months), with routine endoscopic examination each 2 years with multiple biopsies, in patients with BE without dysplasia. 48 patients were diagnosed with any grade of dysplasia on FU endoscopic biopsies. The biopsies were reviewed by specialized pathologists and evaluated epidemiologic data, clinical or surgical treatment for the GERD and about the confirmation, downgrade or upgrade of dysplasia degree. Results: 48 patients were reviewed, 32 males. The medium age was 61, 9 YO (29 -93). Only 18 patients were in follow-up after surgical treatment for GERD. 9 patients had first diagnosis of in situ Adenocarcinoma, after review 8 were confirmed and treated and 1 were downgrade to HGD. 8 patients had first HGD and after review, 2 were upgrade to Adenocarcinoma, 4 were confirmed as HGD (endoscopic treatment) and 2 downgraded to no dysplasia BE. 31 patients had first LGD. 2 had upgrade to HGD/Adeno, 8 are in FU annually and 21 were downgrade to non dysplastic BE. Conclusion: The diagnosis of dysplasia in BE remains a challenge. 23 of 48 (47%) of our patients once marked with any grade of dysplasia, were downgrade after pathological review and FU to non dysplasic BE. These difficulty of appropriate dysplasia degree diagnosis could make some mistakes in BE treatment and surveilance.